Intervensi Koroner pada pasien Angina Pektoris Stabil: Penggunaan Fractional Flow Reserve sebagai Alat Pengambil Keputusan Angioplasti - Januar Wibawa Martha (The Indonesian Heart Association, 2013)
Coronary angioplasty is a definitive, percutaneous intervention to improve myocardial oxygen supply. The benefit of coronary angioplasty for stable angina pectoris is still a controversy. The COURAGE trial had shown that angioplasty for stable angina pectoris gave no additional benefit compared with optimal medical therapy, while the recently done FAME II trial showed the opposite. FAME II trial proved that angioplasty could reduce MACEs in stable angina pectoris patients. The conflicting results from COURAGE and FAME II trials is due to the difference in decision making methodology used for angioplasty. COURAGE used plain angiogram while FAME II utilized Fractional Flow Reserve (FFR) as a tool to decide whether a lesion should undergo angioplasty. The result of FAME II demonstrate FFR is far more reliable to determine coronary lesion which cause ischemia, hence a better decision making tool for angioplasty. The specificity of FFR is proven high, while angiography has an excessive false positives. The use of FFR before angioplasty is still low although there is a considerable evidence that FFR is a better decion making tool for angioplasty compared to angiography. Health economic analysis displayed the use of FFR for stable angina pectoris is cost effective in the long term.